1997
DOI: 10.1007/s004270050113
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster homologue of the hsp60 gene is encoded by the essential locus l(1)10Ac and is differentially expressed during fly development

Abstract: The hsp60 (heat-shock protein 60) gene family of molecular chaperones has been a subject of study in numerous systems due to its important role in the correct folding of non-native proteins in development as well as after heat-shock treatment. Here we present the characterization of the first Drosophila hsp60 homologue. Drosophila HSP60 is most closely related (72% identity across the entire protein sequence) to the mouse mitochondrial HSP60. Western blot experiments indicate that Drosophila HSP60 is enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Transcripts of Hsp60A and Hsp60C genes show low abundance in eye disc cells (Kozlova et al 1997;Sarkar and Lakhotia 2005) while Hsp60B is reported to express only in male germ cells (Timakov and Zhang 2001). However, information available in the databases on the expression of specific genes in different tissues of D. melanogaster (e.g., http://flybase.org or http://www.ncbi.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Transcripts of Hsp60A and Hsp60C genes show low abundance in eye disc cells (Kozlova et al 1997;Sarkar and Lakhotia 2005) while Hsp60B is reported to express only in male germ cells (Timakov and Zhang 2001). However, information available in the databases on the expression of specific genes in different tissues of D. melanogaster (e.g., http://flybase.org or http://www.ncbi.…”
Section: Discussionmentioning
confidence: 98%
“…The Berkeley Drosophila Genome Project has reveled four Hsp60 genes, named as Hsp60A, Hsp60B, Hsp60C, and Hsp60D, respectively (Sarkar and Lakhotia 2005). Studies in our and other laboratories have shown that the Hsp60A, Hsp60B, and Hsp60C proteins have distinct functions in normal development (Kozlova et al 1997;Perezgasga et al 1999;Timakov and Zhang 2001;Lakhotia 2005, 2008;Sarkar et al 2006). …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hsp60 is able to substantially accelerate procaspase-3 maturation by different upstream activator caspases (Xanthoudakis et al 1999). The possible roles of Hsp60 in certain cellular processes, such as sperm cell differentiation, reproduction development, and environment stress response, have also been elucidated by other researches (Meinhardt et al 1995;Paranko et al 1996;Kozlova et al 1997;Neuer et al 2000;Qian et al 2012). Much of the research on organism protection under environmental stress in the last decades has examined the involvement of Hsp60 in multiple pathophysiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Using MitoProt II for Unix (Claros and Vincens 1996), it was possible to predict the mitochondrial signal sequence indicating, with a probability of P ϭ 0.96, that Cpn60 is indeed exported to the mitochondria (see Fig 1, panel A). The presence of a putative targeting signal that is responsible for the translocation into the mitochondrial matrix has also been reported in Cpn60 of Drosophila melanogaster (Kozlova et al 1997), Trypanosoma cruzi (Giambiagi-de Marval et al 1993), Culicoides variipennis (Abdallah et al 2000) and Paracentrotus lividus (Gianguzza et al 2000) and others. The deduced amino acid translation displays a considerable sequence identity (75%) and similarity (87%) to the Cpn60s from C elegans and C briggsae (Fig 1, panel B).…”
Section: Identification Of Cpn60 In P Acuminatusmentioning
confidence: 80%